Identity markers of a boat - Mumbai Archive Project Team (Jio Institute, 2024)
The boat’s bright colours make it easy to spot at sea. Each boat has a unique name, often including the owner’s name and registration number. Small boats usually have a powerful motor, which provides power to steer the boat at sea.